CLINICAL PHARMACOLOGICAL APPROACH TO THE USE OF NEUROLEPTIC DRUGS IN DEPRESSIVE SYNDROME (Multidisciplinary Journal of Science and Technology, 2025)
The clinical use of neuroleptic (antipsychotic) drugs in depressive syndromes represents a complex intersection between psychopharmacology and clinical psychiatry. Traditionally employed in the management of psychotic disorders, certain neuroleptic agents have demonstrated significant efficacy as adjuncts or augmenting agents in depressive disorders, particularly those resistant to conventional antidepressant therapy. Their pharmacological effects extend beyond dopamine receptor antagonism, encompassing modulation of serotonergic, noradrenergic, and glutamatergic neurotransmission. This article examines the pharmacodynamics, pharmacokinetics, clinical applications, and safety considerations of neuroleptic drugs in depressive syndromes, highlighting both their therapeutic potential and the challenges associated with their use.